2020
DOI: 10.1002/jbt.22522
|View full text |Cite
|
Sign up to set email alerts
|

Decision making for promising quinoline‐based anticancer agents through combined methodology

Abstract: During the development of effective drugs for the treatment of cancer, one of the most important tasks is to identify effective drug candidates having maximum antiproliferation and minimum side effects. This paper considers the problem of selecting the most promising anticancer agents, showing inhibition at low IC50 concentration and low releasing lactate dehydrogenase percentage (cytotoxicity). Recently, we prepared quinoline analogs bearing different functional groups and determined their anticancer potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
5
0
4
Order By: Relevance
“…In that study, MCDM results were both consistent with experimental results and suggested that two brominated quinolines can be promising anticancer agent against HeLa, HT29 and C6 cell lines and used in further anticancer preclinic studies. [28] The consistent and effective results obtained in this study [28] motivated us to apply combined MCDM approach for the brominated indeno [1,2-b] quinoline amines in terms of some evaluation criteria. Five parameters of bioactive brominated indeno [1,2-b]quinoline 6, were determined by a decision maker as the key criteria for determining promising anticancer agents against the A549, HeLa, Hep3B and MCF7 cancer cell lines.…”
Section: Evaluation Of the Priorities Of Compounds In Terms Of Anticancer Potentials By Mcdmmentioning
confidence: 52%
See 2 more Smart Citations
“…In that study, MCDM results were both consistent with experimental results and suggested that two brominated quinolines can be promising anticancer agent against HeLa, HT29 and C6 cell lines and used in further anticancer preclinic studies. [28] The consistent and effective results obtained in this study [28] motivated us to apply combined MCDM approach for the brominated indeno [1,2-b] quinoline amines in terms of some evaluation criteria. Five parameters of bioactive brominated indeno [1,2-b]quinoline 6, were determined by a decision maker as the key criteria for determining promising anticancer agents against the A549, HeLa, Hep3B and MCF7 cancer cell lines.…”
Section: Evaluation Of the Priorities Of Compounds In Terms Of Anticancer Potentials By Mcdmmentioning
confidence: 52%
“…In our recent study, the AHP-TOPSIS combination has been used for identifying the most promising anticancer agents against HeLa, HT29 and C6 cell lines with an accurate prediction approach for the first time of the literature. [28] In this study, the effects of seven promising anticancer quinoline compounds on three different types of cancer cell lines were evaluated according to four criteria (IC 50 value, LDH cytotoxicity, DNA laddering feature for apoptosis and topoisomerase I enzyme inhibition) by MCDM. In that study, MCDM results were both consistent with experimental results and suggested that two brominated quinolines can be promising anticancer agent against HeLa, HT29 and C6 cell lines and used in further anticancer preclinic studies.…”
Section: Evaluation Of the Priorities Of Compounds In Terms Of Anticancer Potentials By Mcdmmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] kronik rahatsızlığı olan kişiler için sanal bakımın önemini anlatırken Sun vd. [9] Mobil sağlık platformu üzerinden Covid- 19 Literatürdeki karar problemlerinde ise etkin sonuçların bulunmasını sağlayan ÇKKV yöntemleri ile anti-kanser ajanı [18], insansız hava araçları [19], medikal cihaz [20], ekipman [21,22], makine [23] ve proje [24]…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Çünkü uygulama aşamaları anlaşılır, kısa süreli ve kolay olan bu yöntemler, karar sürecini probleme etki eden tüm parametrelerin dikkate alınmasını sağlayarak yapılandırmakta, karar vericilerin ölçülemeyen düşüncelerini de probleme yansıtmaya olanak sağlamakta ve bu sayede kabul edilebilir ve gerçek hayatla tutarlı sonuçlar vermektedir [3]. Bu doğrultuda, problemlerin bu yapıda olduğu sağlık [4,5], ulaşım [6,7], bakım [8], tedarik [9,10] ve enerji [11] gibi birçok farklı alanlarda da çok kriterli karar verme yöntemlerine başvurulduğu akademik çalışma ile de kanıtlanmıştır. Belirtilen bu avantajları sebebiyle, enerji kaynak alternatiflerinin karşılaştırılması için literatürde çok kriterli karar verme yöntemleri Çizelge 1.…”
Section: Gi̇ri̇ş (Introduction)unclassified